The effect of Yttria-Stabilized Zirconia (YSZ) addition on the synthesis of? ETA-Tricalcium Phosphate (?-TCP) from biogenic hydroxyapatite - Ismail Zainol (Tanjung Malim, 2023)
The effect of Yttria-Stabilized Zirconia (YSZ) addition on the synthesis of? ETA-Tricalcium Phosphate (?-TCP) from biogenic hydroxyapatite by Ismail Zainol